Severe Sepsis and Septic Shock - Angus, Derek C; van der Poll, Tom (The New England journal of medicine, 2013)
Sepsis, a complex physiological and metabolic response to infection, is a common reason for admission to an intensive care unit. This review examines the basis, diagnosis, and current treatment of this disorder. Sepsis is one of the oldest and most elusive syndromes in medicine. Hippocrates claimed that sepsis (σήψις) was the process by which flesh rots, swamps generate foul airs, and wounds fester. 1 Galen later considered sepsis a laudable event, necessary for wound healing. 2 With the confirmation of germ theory by Semmelweis, Pasteur, and others, sepsis was recast as a systemic infection, often described as “blood poisoning,” and assumed to be the result of the host's invasion by pathogenic organisms that then spread in the bloodstream. However, with the advent of modern antibiotics, germ theory did not fully explain the pathogenesis of . . .